2023
DOI: 10.3390/molecules28031398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-Selenium on Nutritional Quality of Cowpea and Response of ABCC Transporter Family

Abstract: It is an important way for healthy Selenium (Se) supplement to transform exogenous Se into organic Se through crops. In the present study, Vigna unguiculata was selected as a test material and sprayed with biological nano selenium (SeNPs) and Na2SeO3, and its nutrient composition, antioxidant capacity, total Se and organic Se content were determined, respectively. Further, the response of ABC transporter family members in cowpea to different exogenous Se treatments was analyzed by transcriptome sequencing comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…ABC transporters have been implicated in Se accumulation and transport in rice, and were detected after SeO 3 2− treatment, suggesting their potential involvement in Se accumulation and transport ( Kong et al., 2021 ). ABCC11, ABCC13, and ABCC10 engage in nano-selenium accumulation and transport in cowpeas ( Li et al., 2023 ). ABC transporter G family member 36 in alfalfa leaves is significantly upregulated after Se treatment, suggesting its involvement in the movement of Se into the leaf tissue ( Wang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABC transporters have been implicated in Se accumulation and transport in rice, and were detected after SeO 3 2− treatment, suggesting their potential involvement in Se accumulation and transport ( Kong et al., 2021 ). ABCC11, ABCC13, and ABCC10 engage in nano-selenium accumulation and transport in cowpeas ( Li et al., 2023 ). ABC transporter G family member 36 in alfalfa leaves is significantly upregulated after Se treatment, suggesting its involvement in the movement of Se into the leaf tissue ( Wang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters may also be involved in Se absorption and transport in plants. ABCC11, ABCC13, and ABCC10 are implicated in the accumulation and transportation of nanoselenium in cowpeas, regulating Se absorption and transformation ( Li et al., 2023 ). Studies indicate that Se may regulate the expression levels of GSTs, affecting transcription factor activity or participating in signal transduction pathways ( Zheng et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In rice, ABC transporters were detected under the Na 2 SeO 3 treatment, indicating that they might participate in Se accumulation and transportation ( Kong et al., 2021 ). Meanwhile, the ABCB, ABCC, and ABCG transporters have been suggested to be involved in the accumulation and transport of Se in cowpeas ( Li et al., 2023 ). Fourteen upregulated ABC genes were also found in our study ( Figure 4 ), including ABCA , ABCB , ABCC , and ABCG , indicating that they may play vital roles in the accumulation and transportation of Se in tea roots.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CNGC1 is a cyclic nucleotide-gated ion channel, and its high expression mediates the physiological and biochemical response of dandelion in the transport of Se to plant root cells under Na 2 SeO 3 treatment (Figure 12). In contrast to previous studies [12,34,48,50,52], the identification of these genes in dandelions treated with selenium offers valuable insights into the molecular mechanisms underlying selenium absorption and transport in crops, thus providing new supplements to the existing knowledge in this field.…”
Section: The Molecular Mechanism Of Organic Se Conversion In Dandelionmentioning
confidence: 91%
“…ABC transporters are a class of transmembrane transporters that utilize the energy generated by ATP hydrolysis to extensively transfer various chemical substrates [51]. Li's research indicated that ABC transporters play a positive role in Se absorption response, with ABCB, ABCC, and ABCG subfamilies playing important roles in Se absorption and transport in cowpeas [52]. Chen's research found that after spraying Na 2 SeO 3 on the leaves of the B. papyrifera, the expression levels of ABC transporters such as ABC11 and ABC5 were significantly upregulated, indicating that these genes may be involved in the transport of Na 2 SeO 3 to vacuoles [53].…”
Section: The Molecular Mechanism Of Organic Se Conversion In Dandelionmentioning
confidence: 99%